Financial Distress and the Cross‐section of Equity Returns - GARLAPPI, LORENZO; YAN, HONG (Journal of Finance, 2011)
ABSTRACT We explicitly consider financial leverage in a simple equity valuation model and study the cross‐sectional implications of potential shareholder recovery upon resolution of financial distress. Our model is capable of simultaneously explaining lower returns for financially distressed stocks, stronger book‐to‐market effects for firms with high default likelihood, and the concentration of momentum profits among low credit quality firms. The model further predicts (i) a hump‐shaped relationship between value premium and default probability, and (ii) stronger momentum profits for nearly distressed firms with significant prospects for shareholder recovery. Our empirical analysis strongly confirms these novel predictions.